2023
DOI: 10.1021/acs.orglett.3c02507
|View full text |Cite
|
Sign up to set email alerts
|

α-Tertiary Primary Amine Synthesis via Photocatalytic C(sp3)–H Aminoalkylation

Hongping Zhao,
Yuanyuan Hu,
Songlin Zheng
et al.

Abstract: Facile access to sterically hindered α-tertiary primary amines via photocatalytic radical coupling of native C(sp 3 )−H substrates with N-unsubstituted ketimines is reported. LiBr was used as a hydrogen atom transfer reagent to cleave C(sp 3 )−H bonds to get alkyl radicals. The in situ-generated HBr can then serve as a Bronsted acid to activate N-unsubstituted ketimines readily for single-electron reduction to deliver α-amino radicals. As a consequence, radical−radical coupling affords primary amines with a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Next, fluorescence quenching experiments showed that only n Bu 4 NBr can significantly quench the excited state of Ir­[dF­(CF 3 )­ppy] 2 (dtbbpy)­PF 6 (Figures S3–S5). In addition, the results of CV measurements (Figures S6 and S7) indicated that n Bu 4 NBr (the onset potential for oxidation is approximately +0.66 V vs SCE in MeCN) can be oxidized by Ir­[dF­(CF 3 )­ppy] 2 (dtbbpy)­PF 6 * ( E ox,1/2 = +1.21 vs SCE in MeCN), and 1a (the onset potential for reduction is approximately −1.16 V vs SCE in MeCN) can be reduced by the reduced form of the photocatalyst Ir II ( E red,1/2 = −1.37 V vs SCE in MeCN).…”
mentioning
confidence: 99%
“…Next, fluorescence quenching experiments showed that only n Bu 4 NBr can significantly quench the excited state of Ir­[dF­(CF 3 )­ppy] 2 (dtbbpy)­PF 6 (Figures S3–S5). In addition, the results of CV measurements (Figures S6 and S7) indicated that n Bu 4 NBr (the onset potential for oxidation is approximately +0.66 V vs SCE in MeCN) can be oxidized by Ir­[dF­(CF 3 )­ppy] 2 (dtbbpy)­PF 6 * ( E ox,1/2 = +1.21 vs SCE in MeCN), and 1a (the onset potential for reduction is approximately −1.16 V vs SCE in MeCN) can be reduced by the reduced form of the photocatalyst Ir II ( E red,1/2 = −1.37 V vs SCE in MeCN).…”
mentioning
confidence: 99%
“…While the transition-metal-catalyzed C­(sp 2 )–H functionalization reactions have been extensively explored, the functionalization of C­(sp 3 )–H bonds is more challenging due to the low reactivity and selectivity. In this context, benzylic C–H bonds are ubiquitous in naturally occurring molecules, pharmaceuticals, agrochemicals, and functional materials; therefore, it has attracted extensive interest to develop diverse strategies for the direct functionalization of benzylic C–H bonds . Especially, alkylarenes are abundant, readily available chemical feedstocks, and they have been used as versatile synthons in organic synthesis.…”
mentioning
confidence: 99%